2015
DOI: 10.1096/fj.14-268987
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation of ubiquitin‐associated protein 2‐like is required for the accurate distribution of chromosomes

Abstract: Proper bioriented attachment of microtubules and kinetochores is essential for the precise distribution of duplicated chromosomes to each daughter cell. An aberrant kinetochore-microtubule attachment results in chromosome instability, which leads to cellular transformation or apoptosis. In this article, we show that ubiquitin-associated protein 2-like (UBAP2L) is necessary for correct kinetochore-microtubule attachment. Depletion of UBAP2L inhibited chromosome alignment in metaphase and delayed progression to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 50 publications
8
50
0
Order By: Relevance
“…In Drosophila, the UBAP2L ortholog has been shown to associate with the RNA-binding protein FMR1 (2). We (unpublished data) and others have confirmed this interaction by mass spectrometry experiments in human cells (8). UBAP2L has also been identified as an RNA-binding protein in human cell lines and mouse embryonic stem cells (19).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In Drosophila, the UBAP2L ortholog has been shown to associate with the RNA-binding protein FMR1 (2). We (unpublished data) and others have confirmed this interaction by mass spectrometry experiments in human cells (8). UBAP2L has also been identified as an RNA-binding protein in human cell lines and mouse embryonic stem cells (19).…”
Section: Discussionsupporting
confidence: 70%
“…Studies have shown that the depletion of UBAP2L suppresses migration and proliferation of prostate cancer cells and inhibits growth of human glioma and colorectal carcinoma cells (5)(6)(7). Recently, it has been shown that the arginine methylation of UBAP2L by protein arginine N-methyltransferase 1 is required for the proper distribution of chromosomes during mitosis (8). Moreover, we have shown that UBAP2L interacts with the Polycomb group protein B lymphoma Mo-MLV insertion region 1 homolog (BMI1), a well-known determinant of hematopoietic stem cell function.…”
mentioning
confidence: 99%
“…In vitro methylation was conducted following combined instructions as described previously [20,31]. Briefly, HA-PRMT1 was purified from HEK293 cells using a protein G Sepharose column, and then reacted with 1 μl of recombinant UBAP2L (Origene, Beijing, China), 80 μM S-adenosylmethionine (NEB, Beijing, China), and 1 × PBS in a reaction volume of 30 μl.…”
Section: In Vitro Methylation Assaymentioning
confidence: 99%
“…Numerous studies indicated its association with various types of cancer [25][26][27][28][29][30]. It is required for the accurate distribution of chromosomes during mitosis [31]. A recent study suggested that it is involved in SG formation [32]; however, the cellular and molecular mechanisms underlying the role of UBAP2L in the regulation of SG assembly and disassembly need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…UBAP2L interacts with the polycomb complex protein B lymphoma Moloney murine leukemia virus insertion region 1 (BMI1) to maintain hematopoietic stem cell activity [17] and plays an important role in the progression of mitosis by correcting kinetochore-microtubule attachment [18]. BMI1 is a well-known polycomb group (PcG) protein that has been reported to be associated with the EMT of cancer cells [19].…”
Section: Introductionmentioning
confidence: 99%